Microwave-Based Rapid Green Synthesis of Gold Nanoparticles Utilizing a Notorious Weed (Mikania micrantha) Extract and Evaluation of their Biomedical Properties - Das S.; Dwivedi A.; Tiwari V.; Yadav V.; Satpathy S.; Mohapatra D.; Sahu A.N.; Kazi M.; Hussain M.D.; Goyal M.; Mukherjee S.; Khan A.; Mandal V.; Nur-e-Alam M.; Patra A. (My University, 2025)
Purpose: The present study aimed to develop and optimize a microwave-assisted quick, single-step, cost-effective, eco-friendly, and safe method for synthesis of gold nanoparticles (AuNPs) by using a notorious weed, Mikania micrantha (Asteraceae), and to investigate its biomedical applications. Methods: M. micrantha AuNPs (MMAuNPs) were produced in 75 s under microwave irradiation. The UV-Vis spectroscopy, SEM, HR-TEM, SAED, EDX, FTIR, XRD, and DLS analyses were used to characterize the synthesized AuNPs. DPPH and ABTS radical scavenging assays were used to determine the antioxidant potential. Anticancer potential was assessed by MTT assay against breast cancer cells. Actophotometer and tail immersion tests were used on Swiss albino mice to evaluate whether MMAuNPs could pass the blood-brain barrier or not. Results: The synthesis of MMAuNPs was confirmed by a characteristic ruby red coloration and surface plasmon resonance peak at 534 nm. The MMAuNPs are predominantly spherical in shape, small (107.82 nm), and crystalline in nature. The antioxidant properties of the MMAuNPs were found to be better than M. micrantha aqueous extract. MMAuNPs showed anticancer potential with IC50 values of 157.1 and 174.2 µg/mL against MCF-7 and MDA-MB-231, respectively. MMAuNPs did not show any significant response of locomotor count and antinociceptive activity. Conclusion: MMAuNPs exhibited potential antioxidant and anticancer activities. However, more investigation is necessary to evaluate the in vivo effects and mechanism of action prior to widespread use of MMAuNPs in the field of medicine, whether as independent therapies, antioxidant, or anticancer substances, or as drug carriers. © The Author(s), under exclusive licence to Springer Nature B.V. 2024.